2020
DOI: 10.1080/23746149.2020.1823880
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal engines for innovative tests of information thermodynamics

Abstract: Recent theoretical developments in information thermodynamics elucidated the link between the acquired information and the entropy production through measurement and feedback control by generalizing the fluctuation theorems and the second law of thermodynamics. We summarize here our recent experimental studies based on the colloidal system that have been conducted to test the theoretical findings of information thermodynamics. In particular, we present the design principles of error-free and noisy information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…For our macroscopic experimental apparatus, the operating costs dwarf the engine output; however, several studies have shown that the fundamental, unavoidable information costs in similar contexts can be much lower (43)(44)(45)(46)(47). In the limits of infinite sampling frequency and signal-to-noise ratio (SNR), different ways of estimating costs (24)(25)(26)48) all lead to vanishing efficiency when applied to our setup. We have not here specified the details of our feedback controller, but one reasonable choice is to allow each new measurement to overwrite the previous one.…”
Section: Discussionmentioning
confidence: 99%
“…For our macroscopic experimental apparatus, the operating costs dwarf the engine output; however, several studies have shown that the fundamental, unavoidable information costs in similar contexts can be much lower (43)(44)(45)(46)(47). In the limits of infinite sampling frequency and signal-to-noise ratio (SNR), different ways of estimating costs (24)(25)(26)48) all lead to vanishing efficiency when applied to our setup. We have not here specified the details of our feedback controller, but one reasonable choice is to allow each new measurement to overwrite the previous one.…”
Section: Discussionmentioning
confidence: 99%
“…While these machines often cannot be categorized as heat engines, the thermodynamic uncertainty relations should still limit their performance in terms of transport coefficients, their fluctuations, and transport efficiency. Of particular interest are processes driven by information [22,23,[80][81][82] and transport in systems of many interacting particles [146]. Another twist in the theory is expected for systems in contact with non-equilibrium reservoirs, where the very definitions of work and heat are still subjects of keen discussions [45,46,[147][148][149][150][151], and thus the results valid for cyclic and steady-state heat engines operating with equilibrium reservoirs cannot be taken for granted.…”
Section: Discussionmentioning
confidence: 99%
“…the role of coupling between system's internal degrees of freedom [77], many-particle gas models of a cylinder enclosed by a piston and coupled to a thermostat [78], and a system of interacting unicyclic machines undergoing a phase transition [79]. For feedback cooling techniques, the concept of fluctuating efficiency was reformulated in terms of fluctuating information flows [80][81][82]. The fluctuating efficiency was also introduced for quantum machines, see e.g.…”
Section: Fluctuating Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Models of that type can be, for example, used to design optimal driving level maximizing performance of a mechanical device. Also, different variants of stochastic diffusion processes with resetting may be realized today experimentally with colloidal particles in a flow chamber 30 or optical tweezers 31 . This opens the possibility of verification tests for many theoretical investigations of resetting mechanisms, their further developments and applications.…”
Section: Discussionmentioning
confidence: 99%